Simulating the Impact on the Local Economy of Alternative Management Scenarios for Natural Areas - Stefania Lovo; Paola De Agostini; Francesco Pecci; Federico Perali; Michele Baggio (Fondazione Eni Enrico Mattei (FEEM), 2005)
This working paper estimates the impact on the local economy of the High Garda Natural Park of alternative management scenarios for the West Garda Regional Forest. The local economy is specialized in tourist services and strongly linked to the tourist presence and their level of expenditure. We wish to investigate the effects of the participative management strategy, which takes into account users preferences and the non-participative strategy, using the SAM multiplier analysis. The local SAM has been constructed considering three sectors: agriculture, tourism and a third aggregate sector including all the other activities. The resident population has been divided into two categories: residents employed in the tourist sector and the remaining resident population. The SAM analysis shows that the accounting representation of the local economy is meaningful and that the participative program, if chosen by the central regional management, would be the most desirable program also at the local level.
Keywords: C63; C67; 330; Tourism; SAM; Multiplier analysis